A Technique for Removing Implant-Retained Denture: Direct Relining Complication - İbrahim Duran; Betül Yilmaz; Çağrı Ural (Case Reports in Dentistry)
The aim of this case report is to present a technique for removing the denture which locked to ball-attachment because of excessive hard relining resin material flows around the ball-attachment. An alternative method was used in the present case. A cylindrical resin was removed with a diamond bur at the level of matrix and by this way the matrix was removed safely. The advantage of the presented method is that it may be extended to other clinical situations when facing a similar complication for implant supported dentures and also that the technique is simple and does not require special equipment.